FACTORS THAT HINDER STRATEGY IMPLEMENTATION IN PUBLIC SECONDARY SCHOOLS: A CASE STUDY OF NAKURU MUNICIPALITY - Mutai, Nixon Kiplagat; Wakogi, Juma; Kwasira, Josphat (European Journal of Business and Strategic Management, 2019)
Purpose: The purpose of this study was to examine the factors that influence strategy implementation in secondary schools within Nakuru Municipality in Kenya. Methodology: The study targeted secondary schools within the municipality. A stratified random sampling design was used in the study to select the respondents from school heads/principals, head of departments (HODs) and section heads. The researcher used a questionnaire to collect data. The questionnaire comprised of both open and closed ended question .The sample size was 100 respondents. A pilot study was carried out in schools in Baringo Municipality. Data analysis was done using Statistical Package for Social Sciences (SPSS) version 17.The final data was presented using tables. A Governmental permit and a letter of introduction from Jomo Kenyatta University were obtained from each respective institution. Respondent's confidentiality was be maintained during the research undertaking. Results: The study found that the management has a high positive correlation with a p< than .05 making it a significant variable. The motivation variable was also positive but at lower rate of 40% and significant with a p<.05. In conclusion, though the school was affected by external factors, management has got a hand in dealing operational activities within the institution. As a result therefore, school management plays a pivotal role in the entire formulation and implementation plan in the institute and the flow of the processes. Distinctive contribution to theory, practice and policy contribution: The study recommends that there should be a common basic structure to all secondary schools to reduce contradiction and conflicts from within and without the institution. Further, stakeholders should synergies with the school head in conjunction with the employees within the organization to ensure a successful strategic implementation. Keywords: Structure, staff motivation, management style, stakeholder, strategy implementation